Editoras universitárias brasileiras e livros em acesso aberto: publicação, modelos de negócio e políticas editoriais - Amaral, Fatima Beatriz Manieiro do (Universidade Federal de São Carlos, 2022)
Alligned with global trends in scientific and academic book publishing, Brazilian university presses are working to make a part of their e-books catalogue available in open access. The purpose of this research is to describe the operation of Brazilian University Presses regarding e-book publishing in open access. In total, 92 academic publishers related to Brazilian higher education and public research institutions were elected as participants in this research. In order to achieve the aforementioned objective, the methodology used was descriptive in nature, with data collection based on document search and analysis of the editorial policies available on the Brazilian university press websites. In addition, a survey was conducted to capture the opinions and experiences of these institutions regarding open access publishing. The results indicate that 94.6% of the participating presses publish in open access, exclusively or associated with the commercialization of books. The business models adopted to finance the publishing activities and the open publications were analyzed: subsidy model, cross-subsidies, grants, shared infrastructure, endowments, book processing charge, liberation, hybrid print model, delayed open access and library based publishing. The most recurring experience related to open access among the presses researched is the high number of downloads. Brazilian university presses realize that it would be good to expand the open access publishing currently available, however, this practice depends on the receipts of funds directed to these books and the expansion of the editorial teams involved, which are currently quite modest in size. Based on the literature reviewed on university presses, the universe of scientific books in open access, and also from the analysis of the results, some recommendations have been elaborated aiming to contribute to the increase in open access e-book publishing by Brazilian university presses, such as: experimentation of other business models, adoption of an adequate technological infrastructure to support open access and to obtain indicators of use and impact, and specially, to systematize the open access practices in its publishing policies. Brazilian university presses are important vehicles for scientific communication and they aggregate good reputation to themselves since they indicate trends and changes in the areas of knowledge, in addition to offering valuable publishing experiences for new authors, and also, they can be pedagogical and innovation spaces for publishing.
Brazilian university presses and open access books: publishing, business models and editorial policies
Keywords: Comunicação científica; Editoras universitárias brasileiras; Acesso aberto; Modelos de negócio; Scientific communication; Brazilian academic publishers; Open access; Business models; E-books; Brazilian university presses; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO